Answer:
x = -1 and x = 7
Step-by-step explanation:
2x^2 + 2x - 14x - 14
2x^2 - 12x -14
Divide through by 2 to simplify the expression
x^2 - 6x - 7
x^2 - 6x -7
Now, let's think of two numbers that when added up gives -6 and when multiplied gives -7
Yes! It's -7 and +1
-7 + 1 = -6 , and -7* 1 = -7
Now, lets substitute these numbers in the expression
x^2 -7x + x - 7
factorize
x(x - 7) + 1(x - 7)
(x + 1) (x - 7)
Now equate to zero
(x + 1) (x - 7) = 0
x + 1 = 0
subtract 1 from both sides
x +1 - 1 = 0 -1
x = -1
Also,
x - 7 = 0
Add 7 to both sides
x -7 + 7 = 0 + 7
x = 7
Hence, x = -1 and x =7
Are you looking for the value of x?
We can complete the square/factor:
x^2+7x-30=0
(x+10)(x-3)=0
By the zero product property rule, we have two equations, x+10=0 and x-3=0.
So the zeroes of x are -10 and 3
Hope this helped. Comment below if this didn't make sense.
Answer:
3/5
Step-by-step explanation:
3/5 x 2/5 = 6/25
Step-by-step explanation:
<u>5</u><u>)</u><u> </u>2.4×10^-5 / 4.5×10^-11
- 2.4×10^-5= 0.000024
- 4.5×10^-11= 0.000000000045
=0.000024/0.000000000045
=24/1 × 1,000,000/45
=24,000,000/45
=533,333.33°
=5.33333°×10^5
**NOT SURE ABOUT THIS QUESTION
<u>6</u><u>)</u><u> </u>(4,-2)
<u>7</u><u>)</u> --------
<u>8</u><u>)</u>
- 2x + 3 = 5x - 2
- 2x - 5x = - 2 - 3
- -3x = -5
- x = -5/-3
- x = 1.66°
- 6x + 4 = 6x + 4
- 2 (2x + 3) = 8x - 2
- 4x + 6 = 8x - 2
- 4x - 8x = -2 - 6
- -4x = -8
- x = -8/-4
- x = 2
- -3x + 2 = -3x + 5
Letter be has no solution because it is broken down as "0x = 0"
Answer:
-4x^2 + 237x - 675
Step-by-step explanation:
(x - 3)*(232 - 4x -7) >> Distribute x and -3 to the trinomial
232x - 4x^2 - 7x - 696 + 12x + 21 >> Simplify
-4x^2 + 237x - 675